Concussion knowledge, attitudes and behaviour in equestrian athletes. Issue 11 (November 2020) - Theadom, Alice; Reid, Duncan; Hardaker, Natalie; Lough, Jules; Hume, Patria A.
Abstract: Objective: To determine knowledge, attitudes and behaviour towards concussion in adult equestrian athletes. Design: Nationwide, cross-sectional, questionnaire. Methods: Participants were recruited via advertisements circulated through social media, community presentations and equestrian organisations. Participants were sent a web link to an online questionnaire previously designed for high school athletes and modified to ensure relevance to equestrian activities. The percentage of correct responses per item and a total knowledge score were calculated. Differences in concussion knowledge by age, sex, level of experience and previous history of concussion were explored using t-tests, 95% confidence intervals (CI) and effect sizes. Results: The questionnaire was completed by 1486 participants (Mean age = 39.1 ± 15.4). Knowledge of what concussion was, how to recognise it and key symptoms (except poor sleep) was high (>80%). In contrast, awareness of guidelines was moderate (56%) and inability of helmets to prevent concussion was low (12%). Significantly higher levels of knowledge of concussion were identified in females compared with males (t=-6.55 p < 0.001, 95%CI=-3.26 to -1.75). The majority (87%) of participants reported that a helmet should be replaced after a fall, yet 46% reported re-using a helmet following a hit to the head. Conclusions: Knowledge of and attitudes towards concussion were positive. However, there were knowledge gaps and discrepancies between some attitudes and behaviour on some aspects of concussion. Targeted campaigns to promote awareness of concussion and improve recognition and onward management are needed. Education related to equestrian activities such as helmet use and injury mechanisms is needed to change behaviour and minimise the risk of injury.